1995
DOI: 10.1182/blood.v86.2.703.bloodjournal862703
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of acute myeloblastic leukemia cells to recombinant human thrombopoietin

Abstract: Thrombopoietin (TPO) is a newly identified hematopoietic growth factor that stimulates both megakaryopoiesis and thrombopoiesis through its interaction with a specific cell surface receptor encoded by the c-mpl proto-oncogene. In an effort to investigate the effect of TPO on human myeloid leukemia cells, the expression of c-mpl and the proliferative response to recombinant human (rh) TPO were investigated in a series of patients with acute myeloblastic leukemia (AML). Of 50 cases of AML, the c-mpl mRNA was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 29 publications
1
36
1
1
Order By: Relevance
“…Expression of c-mpl is restricted to human hematopoietic cells such as megakaryocytes, platelets, CD34+ cells, human AML cells and blasts from myelodysplastic syndrome. In cells from patients with AML, detection of c-mpl mRNA has been reported to have an incidence of 52% (27) or 55% (26). In the present study, 4 of 11 AML case (36%) showed c-mpl mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of c-mpl is restricted to human hematopoietic cells such as megakaryocytes, platelets, CD34+ cells, human AML cells and blasts from myelodysplastic syndrome. In cells from patients with AML, detection of c-mpl mRNA has been reported to have an incidence of 52% (27) or 55% (26). In the present study, 4 of 11 AML case (36%) showed c-mpl mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Quadruplicate aliquots of cells (5x104 cells in 200ml RPMI supplemented with 10% FCS) were cultured in 96-well flat-bottom microtiter plates for 72 h at 37°C in the presence or absence of growth factors. The concentrations value was lower than 0.05 we considered that the proliferative response was significant as previously described (27). We performed morphological analysis of samples before and after stimulation of TPO and certified that proliferating cells were leukemic cells.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…myeloid leukaemic cells grow in the presence of human TPO (Matsumura et al, 1995), and the receptor transcript has been evidenced in several myeloid leukaemic cell lines (Methia et al, 1993). Although TPO stimulates leukaemic cell proliferation, it fails to induce cell differentiation.…”
mentioning
confidence: 99%